Strategy to Improve Supervision Skills Among Site Supervisors in the Construction Industry - Chin Hong, Wong; Ta Wee, Seow; Sarpin, Norliana; Omar, Roshartini (Research in Management of Technology and Business, 2021)
Supervision define as the role of accomplishing things by people and directing human resources as nicely as a group closer to achieve a common goal. In Malaysia, many issues are found in the construction sector in the term of construction site supervision. Because of these problems, work-related accidents resulting in death and injury occur frequently at the construction sites. The major encountered problems are especially adequate knowledge of the newly graduated building site supervisor about their roles and legal obligations despite being in construction sites during construction applications. Therefore, this study was conducted to identify the problems being faced in the construction site without supervision skill and to determine the importance of supervision skills of site supervisors in construction performance. Several effective strategies are suggested to improve the supervision skills among site supervisors thus to increase the construction performance in the industry. The study employed a quantitative method. Questionnaires were distributed to 70 site supervisors in Johor. The Statistical Package Social Science (SPSS) was used to run the descriptive analysis, normality test and Spearman correlation analysis. The findings showed that delay of construction project, time-management and collaboration of supervision team have the highest mean for problem, importance, and strategy respectively in this study. Furthermore, the results indicated that all three strategies had positive relationships with supervision skills. Effective implementation of solutions in supervision skills will help site supervisors have a better future in the construction industry.